Driver Drowsiness Bracelet Using Heart Rate Sensor and Arduino Uno - Lesmana Dwi Prayudha; Uray Ristian; Hirzen Hasfani (CV. Digital Innovation, 2025)
Traffic accidents are incidents on the road that result in material losses or fatalities, and approximately 69.7% of them are triggered by human error. One of the dominant factors is reduced alertness due to drowsiness, which can develop into microsleep—a brief loss of consciousness that often goes unnoticed by drivers. Since microsleep is associated with physiological changes such as a decrease in heart rate during the early phase before falling asleep, heart-rate signals serve as an important indicator for monitoring drowsiness. This study develops a driver drowsiness monitoring system based on a heart-rate sensor packaged in a wristband and controlled by an Arduino Uno. A pulse sensor operating on the Photoplethysmography (PPG) principle is used as the main input, while a signal-filtering mechanism is incorporated to reduce noise caused by hand movement, ensuring stable data quality. The system implementation successfully produced clean and consistent heart-rate signals that can be processed to identify drowsiness indicators without significant interference. Testing results show that the designed system is capable of monitoring heart-rate activity effectively and providing valid indicators of drowsy conditions. Overall, the device demonstrates strong potential as a practical solution to help prevent accidents caused by microsleep.